Embedded opportunities and conflict of subsidiary initiatives. Issue 1 (23rd November 2019) - Ahworegba, Akiebe Humphrey; Colovic, Ana
Abstract : Purpose: The purpose of this paper is to advance understanding of why subsidiary initiative opportunities face constant opposition, despite being essential to the competitiveness of international organizations. The paper also develops a detailed theoretical framework to showcase the conflicts and opportunities created by subsidiary initiatives, as most research in this field is descriptive and comparative. Design/methodology/approach: The paper draws substantially on entrepreneurship, agency, contingency and institutional theories, and focuses on the conflict generated by subsidiary initiatives in the context of headquarters–subsidiaries relationships, including the impact of developed and emerging markets. Based on a thorough analysis of the literature, the paper's conceptual approach aims to develop models of how MNC networks deal with subsidiary initiatives. Findings: The findings indicate that subsidiary initiative opportunities face opposition from both the organization and its environment. Originality/value: The paper builds conceptual models showing the network of opportunities and conflicts created by subsidiary initiatives.